2008
DOI: 10.1007/s11259-008-9054-x
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeletal changes in Eimeria bovis-infected host endothelial cells during first merogony

Abstract: The first merogony of Eimeria bovis takes place in lymphatic endothelial cells of the ileum, resulting in the formation of macromeronts up to 250 microm. In this study, we investigated the host cell cytoskeleton (actin filaments, microtubules, spectrin, vimentin intermediate filaments) associated with parasitic development in vitro by confocal laser scanning microscopy (CLSM) using primary bovine umbilical vein endothelial cells (BUVEC) and bovine spleen lymphatic endothelial cells (BSLEC) as host cells. No pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…A similar feature has also been suggested for the pathogenic species E. bovis and E. zuernii (Kawahara et al, 2010). It is intriguing to verify that despite the different host The phylogenetic proximity of E. arloingi and E. bovis may be in accordance with other common features of parasite-host cell interactions, such as the modulation of host cell-apoptosis (Lang et al, 2009), -cytoskeleton (Hermosilla et al, 2008) and -metabolism (Hamid et al, 2014;Hamid et al, 2015;Silva et al, 2015;Taubert et al, 2010) to guarantee successful macromeront formation.…”
Section: Discussionsupporting
confidence: 61%
“…A similar feature has also been suggested for the pathogenic species E. bovis and E. zuernii (Kawahara et al, 2010). It is intriguing to verify that despite the different host The phylogenetic proximity of E. arloingi and E. bovis may be in accordance with other common features of parasite-host cell interactions, such as the modulation of host cell-apoptosis (Lang et al, 2009), -cytoskeleton (Hermosilla et al, 2008) and -metabolism (Hamid et al, 2014;Hamid et al, 2015;Silva et al, 2015;Taubert et al, 2010) to guarantee successful macromeront formation.…”
Section: Discussionsupporting
confidence: 61%
“…Hermosilla et al [16] reported an increasing influence on actin- and tubulin-related reorganisation of the host cell cytoskeleton with ongoing infection. We now found enhanced gene transcription of several tubulins (TUBB, TUBB4, TUBB6) and of molecules involved in microtubule binding or cytoskeleton organisation (TPPP, DOCK7, CKAP4, DCT3) in the late phase of infection.…”
Section: Discussionmentioning
confidence: 99%
“…This lengthy process (14–18 days) is associated with the enlargement and reorganisation of the host cell (e.g. host cell cytoskeletal elements [16]). Parasite growth and proliferation within the parasitophorous vacuole (PV) requires nutrients from the host cell, as in other apicomplexa [7, 27].…”
Section: Introductionmentioning
confidence: 99%
“…This could serve the acquisition of organelles such as mitochondria and the endoplasm reticulum to the closer vicinity of the E. bovis PV during replication (Hermosilla et al . 2008). In E. bovis infected cells, the transcription levels of several tubulins (TUBB, TUBB4 and TUBB6) were increased.…”
Section: Interactions Of Apicomplexan Parasites With Host Cell Microtmentioning
confidence: 99%
“…Actin surrounds the PV within 3 dpi, and actin filament bundles form a thick layer in the final stages of meront maturation (15–20 dpi) (Hermosilla et al . 2008). Several actin-related genes are upregulated in cells containing developing macromeronts.…”
Section: Actin Filament Dynamics In Cells Infected By Apicomplexamentioning
confidence: 99%